The Influence of Health Education on Breast Milk Management on the Knowledge and Attitudes of Pregnant Women Working in Girimukti Village - Sariestya Rismawati; Tita Rosniawati; Dede Gantini (Poltekkes Kemenkes Tasikmalaya, 2026)
Background: Working mothers are not entirely with their babies during the first six months, which increases the likelihood of not exclusive breastfeeding. This issue can be addressed through breast milk management. Therefore, pregnant women need to understand how to manage expressed breast milk (EBM) to be prepared during the breastfeeding phase. Data from Girimukti Village shows that 27 pregnant women were working, and the coverage of exclusive breastfeeding from January to June 2024 reached 60.75%. Objective: This study aims to determine the effect of health education on EBM management on the knowledge and attitudes of working pregnant women in Girimukti Village, Cisewu Health Center Area, Garut Regency in 2024. Methods: This research employs a quantitative approach with a quasi-experimental design. The study uses a pretest and posttest design. The sample consisted of 28 third-trimester pregnant women in Girimukti Village, selected using total sampling. Data were collected using questionnaires and analyzed using the Wilcoxon test. Results: Knowledge about EBM management before health education was categorized as poor (46.4%), and attitudes were negative (64.3%). After health education, knowledge was categorized as good (60.7%) and attitudes as positive (67.9%). Conclusion: Health education on EBM management significantly influenced knowledge (p = 0.000) and attitudes (p = 0.013) of working pregnant women. Recommendations: Working pregnant women are advised to enhance their knowledge of EBM management to ensure they can provide exclusive breastfeeding for their babies during the breastfeeding period.